Windows phone application sketch book - Kaplan, Dean (Apress, 2011)
Think you have the next great Windows Phone app idea? The Windows Phone Application Sketch Book is an essential tool for any aspiring Windows Phone developer. This sketch book makes it easy to centralize and organize your ideas, featuring enlarged Windows Phone templates to write on. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes and document the app name and screen name. This book is an invaluable tool for bringing your next great Windows Phone app idea to life!